Structures Congress 2014 2014
DOI: 10.1061/9780784413357.064
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Design of Circular Concrete Filled Tube Bridge Pier Connections for Accelerated Bridge Construction

Abstract: Concrete filled tubes (CFTs) consist of a steel tube with concrete infill. CFT columns offer an efficient and economical alternative to conventional reinforced concrete bridge columns, in that CFT columns can offer larger strength and stiffness and facilitate rapid construction. This report is the second in a series. The prior report focused on engineering methods for CFT components and seismically resilient CFT column-to-foundation connections. This report focuses on CFT column-to-cap beam connections. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Bar fracture revealed that the connector's tensile capacity was larger than the capacity of the reinforcing bar. Finally, they concluded that the diameter of the sleeve and the length of the bar would be the sole factors affecting how well the grouted splice sleeve connection performs [25] [26].…”
Section: Connection Of Precast Segmentsmentioning
confidence: 99%
“…Bar fracture revealed that the connector's tensile capacity was larger than the capacity of the reinforcing bar. Finally, they concluded that the diameter of the sleeve and the length of the bar would be the sole factors affecting how well the grouted splice sleeve connection performs [25] [26].…”
Section: Connection Of Precast Segmentsmentioning
confidence: 99%
“…This resulted in different types of column-footing connections, as shown in Figure 6. Non-prestressed connections include, pocket connections, as shown in Figure 6(c) (Stephens et al, 2014), socket connection, as shown in Figure 6(b) (Abdelkarim et al, 2017; Abdulazeez and ElGawady, 2017; Haraldsson et al, 2013; Shen, et al, 2022), grouted rebar duct connection, as shown in Figure 6(d) (Belleri and Riva 2012; Tazarv and Saiidi, 2016; Tong et al, 2022; Zhanghua et al, 2020), splice sleeve bar coupler connection, as shown in Figure 6(a) (Ameli and Pantelides, 2016; Li et al, 2018; Qu et al, 2018; Wang et al, 2018; Zhanghua et al, 2020; Yu et al, 2022; Zhanghua et al, 2020), and emerging type connections (Kim et al, 2015), as shown in Figure 6(e).…”
Section: Constructionmentioning
confidence: 99%
“…Recently, hybrid rocking-bar-pocket connections have been presented to connect pre-tensioned precast column to the cap beam as shown in Figure 7(d) Davis et al (2017) and Mantawy et al (2016). The second type of column to cap-beam connections used non-prestressed connections including pocket connections, as shown in Figure 8(a) Mehrsoroush and Saiidi (2014), and Stephens et al (2014), grouted ducts connections, as shown in Figure 8(e) Wolf and Friedman (1994), Matsumoto et al (2002), Mandawe et al, (2002), and Qu et al (2018), bar couplers connections, as shown in Figure 8(d) Qu et al (2018), emerging connections, as shown in Figure 8(f) Kim et al (2015), and bar splice using ultrahigh-performance concrete (see Figure 8(g)) Shafieifar et al (2020). Zaghi et al (2010) proposed a pipe-pin two-way hinge connection to connect the column with the cap beam (see Figure 8(c)).…”
Section: Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though these elements could offer efficient and economical alternatives in construction of bridge columns, their field implementation is limited because of unreliable connections, especially in seismic zones. CFST is also susceptible to rapid corrosion because of the use of steel tubes in aggressive environments ( 10 , 11 ). The FRP tubes have the advantage of being lightweight, corrosion-resistant and high strength, but the weak interface between the FRP tube and the conventional concrete shows signs of concrete shrinkage and inadequate concrete compaction, reducing its load-bearing capacity ( 12 , 13 ).…”
mentioning
confidence: 99%